Smoking Behavior Among School Students At Al-Doura/Al- Kurkh/Baghdad Year 2014 - Humadi, Abbas Fadhal (AL-Kindy College Medical Journal, 2016)
Background: Most adult smokers start smoking regularly some time before 18 years of age. Cigarette smoking is a major ‘preventable’ cause of morbidity and mortality worldwide. It is well-known that smoking has hazardous effect on many systems like pulmonary and cardiovascular system.Objectives: Study the prevalence of smoking among school pupils according to the mode of smoking, age, school grade, school environment and possible health risk associated with smoking. Type of the study: A cross-sectional study.Methods: Study was conducted between 1st of March 2014 to 30th of May 2014 at Al-Doura/Al- Kurkh/Baghdad by using convenient sample, including all pupils from 6 schools. The schools were 2 secondary schools, 3 intermediate schools and 1 professional secondary school from second Al-Kurkh education directorate. A total of 1258 boy pupils were studied. An anonymous self-completion questionnaire was used. The questionnaire included 15 questions (3 open questions and 12 close questions) about sociodemographic information, smoking information, and possible health disorders associated with smoking. Results: The present study had shown that the prevalence of smoking habits both (12.1% cigarette and 2.3% shisha) increased with age, class grade, and broader school environment. Both cigarette and shisha smoking produce various health disorders among schools' pupils. The results indicate that dry cough more frequent among shisha smoking pupils which was statistically highly significant (P < 0.001).Conclusions: Age, school grade of pupils and broader school environment play the major rule in the increasing prevalence of smoking among pupils, both cigarette and shisha smoking had hazardous effect on pupils' health.